2015
DOI: 10.3109/13880209.2015.1052149
|View full text |Cite
|
Sign up to set email alerts
|

Nephro-protective potential ofMorus alba, a prospective experimental study on animal models

Abstract: The co-administration of M. alba with gentamicin prevented renal functioning alterations expected with the use of gentamicin alone. Therefore, it can be concluded that M. alba to protect from kidney damage, which may be because of its free radical scavenging and diuretic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…There were significant differences between the glycerol (+ve) group and all groups pretreated and treated with grapefruit . These results were in accordance with those previously reported by Ullah et al,(2014)and Sudha and Venkatalakshmi.,(2012).…”
Section: Discussionsupporting
confidence: 94%
“…There were significant differences between the glycerol (+ve) group and all groups pretreated and treated with grapefruit . These results were in accordance with those previously reported by Ullah et al,(2014)and Sudha and Venkatalakshmi.,(2012).…”
Section: Discussionsupporting
confidence: 94%
“…More interest has developed to the protective effects of medicinal plants against chemically induced toxicities (Frei and Higdon, 2003). For example, Azima tetracantha (Konda et al, 2016) and Capparis spinosa (Tlili et al, 2017), Cestrum nocturnum (Saleem et al, 2017), Morus alba (Ullah et al, 2016), Nigella sativa (Begum et al, 2006), Sechium edule (Mumtaz et al, 2012), Terminalia muelleri (Fahmy et al, 2016) show nephroprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…This result was agree with Colker et al, (1999) that in a double-blind, placebocontrolled study of C. aurantium, caffeine and St John's Wort decreased total body weight with strict diet and exercise. and Ullah et al,( 2014) who indicated that the combined administration of C. aurantiumat a dose of 200 mg/kg/day for a period of twenty one days significantly decreased in body weigh. Thus it may be explained by Haaz et al, (2006) who mentioned that antiobesity effect of C. aurantium contains synephrine which is a stimulant with similar properties as caffeine and ephedrine.…”
Section: Discussionmentioning
confidence: 99%